SCHOOL-BASED INTERACTIVE REPRODUCTIVE HEALTH EDUCATION TO IMPROVE ADOLESCENT UNDERSTANDING OF HIV/AIDS - Ela Dyah Indrasti Priwardani; Octavia Catur Wulandari; Sania Salsabila; Adinda Aprilia Putri; Rifadah Amaniyah; Kharisma Bela Ramdani; Elok Permatasari (UNEJ e-Proceeding, 2023)
Background: Adolescence is the genital period or puberty. At this time adolescents have increased curiosity and sexual desire, in contrast to the previous period, namely childhood. Adolescents have reproductive risk vulnerability, one of which is susceptible to accessing risky sexual behavior that has an impact on the transmission of sexually transmitted diseases, especially HIV/AIDS. Promotional and preventive efforts to increase understanding and awareness of adolescent reproductive health need to be carried out in particular to improve adolescent understanding of HIV/AIDS. This study aims to analyze the contribution of schoolbased reproductive health education in an effort to improve adolescents ' understanding of HIV/AIDS. Methods: This study is a pre-experimental one group pre-post design study. Respondents in this study were adolescents in MTs 2 Jember aged 14-15 years who were randomly selected with a large sample of 44 adolescents. Data analysis in this study using descriptive analysis and comparative analysis using paired t-test. Results: The results showed an increased understanding of adolescents about HIV / AIDS, especially about the definition of HIV, the causes of HIV/AIDS, HIV / AIDS treatment, the stages of infection, the prevalence of people and how to prevent it. Most indicators of HIV/AIDS understanding improved after school-based interactive reproductive health education. Statistical test results showed a value of sig = 0.000 which means there were significant differences in adolescents ' understanding of HIV/AIDS before and after Interactive Health Education. Conclusions: School-based interactive reproductive health education has an impact on improving adolescents ' understanding of HIV/AIDS. However, these educational efforts need to be continued with the full support of the school. Keywords: Adolescents, Understanding of HIV / AIDS, Reproductive Health Education